Animal spirits and monetary policy - Paul De Grauwe (Center for Economic Studies and ifo Institute (CESifo), 2008)
We develop a behavioral macroeconomic model in which agents use simple but biased rules to forecast future output and inflation. This model generates endogenous waves of optimism and pessimism (Animal Spirits) that are generated by the correlation of biased beliefs. We contrast the dynamics of this model with a stylized DSGE-version of the model and we study the implications for monetary policies. One of our main results is that strict inflation targeting is suboptimal because it gives more scope for waves of optimism and pessimism to emerge thereby destabilizing output and inflation.
Keywords: E10; E32; D83; 330; DSGE-model; imperfect information; heuristics; animal spirits; Konjunkturtheorie; Dynamisches Gleichgewicht; Allgemeines Gleichgewicht; Sunspot; Geldpolitik; Inflation Targeting; Theorie